2016
DOI: 10.1007/s00259-016-3536-9
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte function following radium-223 therapy in patients with metastasized, castration-resistant prostate cancer

Abstract: The results argue against an impairment of lymphocyte function after Ra therapy. Thus, immune responses against pathogens should remain unaffected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The authors concluded that immune responses against pathogens should remain unaffected by Ra-223. 22 One limitation of this study was whether immune responses were tested after a single or multiple doses of Ra-223. Furthermore, in a preliminary study of 7 patients with mCRPC who received Ra-223, levels of programmed cell death 1 expression decreased on effector memory CD8 þ T cells and memory CD4 þ T cells after Ra-223.…”
Section: Ra-223 Hematologic Effectsmentioning
confidence: 99%
“…The authors concluded that immune responses against pathogens should remain unaffected by Ra-223. 22 One limitation of this study was whether immune responses were tested after a single or multiple doses of Ra-223. Furthermore, in a preliminary study of 7 patients with mCRPC who received Ra-223, levels of programmed cell death 1 expression decreased on effector memory CD8 þ T cells and memory CD4 þ T cells after Ra-223.…”
Section: Ra-223 Hematologic Effectsmentioning
confidence: 99%
“…It is also possible that radium-223 may inhibit B-and T-cell proliferation and function. While a prior small study did not show a negative impact of radium-223 on lymphocyte function (18), that study used different time points to assess immune parameters and did not examine longer term T-cell effects. Thus, radium-223 could have been myelosuppressive, leading to dampened immune responses overall; however, there was no evidence of this detected within the product parameters for sipuleucel-T. Another hypothesis is that genomic alterations could be playing a role, especially if these were not balanced across arms.…”
Section: Discussionmentioning
confidence: 99%
“…It has been published that radiotherapy with beta and gamma isotopes induces numerical and also functional changes in leukocytes [ 11 , 12 , 13 , 14 , 15 ]. In line with only mild effects of 223 Ra, our group showed that in eleven patients with metastasized, castration-resistant prostate cancer one cycle of treatment with this alpha-emitter did not significantly impair lymphocyte function in vitro [ 16 ]. However, in patients with ankylosing spondylitis treatment with 223 Ra led to a reduction of inflammatory responses (C-reactive protein) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…As compared to a single cycle of 223 Ra therapy, consecutive cycles may have an additive effect on hematopoietic toxicity and may thus lead to detectable effects on in vitro immune function in patients with metastatic prostate cancer. Due to its high sensitivity, the lymphocyte transformation test (LTT) is considered the gold standard for the determination of lymphocyte proliferation after irradiation [ 11 , 12 , 14 , 15 , 19 , 20 , 21 , 22 ] and was also used in our previous study on antimicrobial immune function after one cycle of 223 Ra therapy [ 16 ]. The LTT determines cell proliferation by measuring the incorporation of 3 H-thymidine during DNA duplication, e.g., after stimulation with mitogens or recall antigens.…”
Section: Introductionmentioning
confidence: 99%